Legal Protection for Tourists Through Supervision and Law Enforcement Against Illegal Travel Agencies for Sustainable Tourism in Bali Province - Made Setiasa; I Nyoman Putu Budiartha; I Wayan Wesna Astara (Journal Equity of Law and Governance, 2023)
The global expansion of tourism carries social, cultural, and economic significance, necessitating effective management. Legal regulations are instrumental in ensuring justice and societal welfare, encompassing human rights fulfillment for tourists, encompassing quality service, safety, and comfort. This requires collaborative synergy between the government, tourism service providers, local communities, and tourists themselves. Empirical research is employed in this study, amalgamating sociological and legal approaches. Primary data is supported by secondary literature. The research explores legalities surrounding supervision and law enforcement, inadequacies in preventing illegal travel ageny (biro perjalan wisata/BPW), law enforcement strategies against such entities, and governmental efforts for tourist legal protection and sustainable tourism realization. Findings affirm that effective regulation, involving stakeholders' responsibility, is vital for justice in the tourism sector. However, challenges persist in effectively preventing illegal travel agencies despite governmental efforts, resulting in discrepancies between issued permits and operational travel agencies. Law enforcement mechanisms primarily leverage Bali Regional Regulation Number 10 of 2020, especially targeting illegal online operations. To ensure tourist protection and Bali's sustainable tourism, governmental persuasion and prevention strategies are pivotal. The study proposes a policy merger and a travel agency permit moratorium to legalize tourism actors, fostering job creation and societal welfare while preserving sustainable tourism in Bali.